Association between mid‐term worsening renal function and mortality after transcatheter aortic valve replacement in patients with chronic kidney disease. Issue 1 (17th December 2020) - Phan, Derek Q.; Lee, Ming‐Sum; Aharonian, Vicken; Mansukhani, Prakash; Moore, Naing; Brar, Somjot S.; Zadegan, Ray
Abstract: Introduction: Chronic kidney disease (CKD), acute kidney injury (AKI) and worsening renal function at 30 days after transcatheter aortic valve replacement (TAVR) portend poor outcomes. We sought to evaluate the association between worsening renal function at 3–6 months and mortality among patients with baseline renal dysfunction undergoing TAVR. Methods: This is a retrospective study of patients with glomerular filtration rate (GFR) < 60 ml/min undergoing TAVR between June 2011 and March 2019 at the Regional Cardiac Catheterization Lab at Kaiser Permanente Los Angeles. Worsening renal function at 3–6 months post‐TAVR was defined as: increase in serum creatinine >1.5 times compared to baseline, absolute increase of ≥0.3 mg/dl, or initiation of dialysis. Results: Of 683 patients reviewed, 176 were included in the analysis (median age 84 [IQR 79–88] years, 56% female). Of these, 27 (15.3%) had worsening renal function. AKI post‐TAVR (OR 2.9, 95% CI 1.1–7.4, p = .03) and transfusion of ≥4 units red blood cells (OR 8.4, 95% CI 1.2–59, p = .03) were independent predictors of worsening renal function. Worsening renal function increased risk for mortality (HR 2.2, 95% CI 1.17–4.27, p = .015) at a median follow‐up of 691 days. Those with improved/stable function with baseline GFR < 60 ml/min had comparable mortality risk to those with baseline GFR ≥ 60 ml/min (18% vs. 16.5%; HR 1.1, 95% CI 0.72–1.75, p = .62). Conclusion: Among patients with baseline renal dysfunction, only 15% developed worsening renal function at 3–6 months after TAVR, which was associated with increased mortality. Predictors for worsening renal function include AKI and blood transfusions. Preventative measures peri‐procedurally and continued monitoring post‐discharge are warranted to improve outcomes.